Excellent oxygen evolution reaction of NiO with a layered nanosphere structure as the cathode of lithium–oxygen batteries. Issue 7 (16th January 2018) - Dong, Hongyu; Tang, Panpan; Zhang, Shiquan; Xiao, Xinglu; Jin, Cheng; Gao, Yicong; Yin, Yanhong; Li, Bing; Yang, Shuting
Abstract : A layered nanosphere structured NiO catalyst was synthesized by a simple and efficient hydrothermal method as a cathode material for lithium–oxygen (Li–O2 ) batteries. Abstract : A layered nanosphere structured NiO catalyst was successfully synthesized by a simple and efficient hydrothermal method as a cathode material for lithium–oxygen (Li–O2 ) batteries. Cyclic voltammetry (CV), dual electrode voltammetry (DECV) and chronoamperometry (CA) by rotating ring-disk electrode (RRDE) were carried out to investigate the catalytic activity of this catalyst for the oxygen evolution reaction (OER). The results revealed that the layered nanosphere NiO exhibited excellent electrochemical performance, stability and a typical four-electron reaction as a cathode electrocatalyst for rechargeable nonaqueous Li–O2 batteries. The overpotential of the NiO is only up to 0.61 V. X-ray photoelectron spectroscopy (XPS) characterization shows that the Li2 O2 and Li2 CO3 formed during the discharge process and decomposed after charging. Moreover, the cut-off voltage of discharging is about 2.0 V in the NiO-based Li–O2 batteries, while the specific capacity is up to 3040 mA h g −1 . There is no obvious performance decline of the battery after 50 cycles at a current density of 0.1 mA cm −2 with a superior limited specific capacity of 800 mA h g −1 . Herein, the layered nanosphere structured NiO catalyst is considered a promising cathode electrocatalyst for Li–O2 batteries.